Characteristics and dynamic changes of gut microbiota in Mongolian horses and Guizhou horses - Li, Yaonan; Lan, Yanfang (Frontiers in Microbiology, 2025)
The gut microbial importance and its crucial roles in host digestion, immunity, and metabolism have received widely attention. Horses, especially indigenous varieties such as Mongolian horses (MGH) and Guizhou horses (GZH), have not received sufficient attention, and the characteristics of their gut microbiota are still unclear. For this purpose, we collected faecal samples from eight MGH and eight GZH to compare their gut microbial differences using amplicon sequencing. The results of alpha diversity analysis indicated that the gut bacterial diversity and gut fungal abundance in GZH were significantly higher than those in MGH. Meanwhile, beta diversity revealed that there were significant differences in the gut bacterial and fungal structures between GZH and MGH. Although the dominant bacterial and fungal phyla of GZH and MGH were the same, there were a large number of significantly different bacteria and fungi between both groups. Moreover, we observed that there were 32 phyla (23 bacterial phyla and 9 fungal phyla) and 718 genera (383 bacterial genera and 335 fungal genera) with significant differences between the GZH and MGH. Notably, this study also revealed some differences in intestinal functions between MGH and GZH, such as chemoheterotrophy, fermentation, and cellulolysis. To our knowledge, this is the first report on the comparative analysis of the gut microbiota between MGH and GZH. Our results demonstrated that GZH have a richer and more diverse gut microbiota compared with MGH. Additionally, these results are important for understanding the gut microbial characteristics of indigenous horse.